Who Can Work from Home? - Vasil Yasenov (Institute of Labor Economics (IZA), 2020)
In response to the COVID-19 pandemic, many states have adopted stay-at-home orders, rendering a large segment of the workforce unable to continue doing their jobs. These policies have distributional consequences, as workers in some occupations may be better able to continue their work from home. I identify the segments of the U.S. workforce that can plausibly work from home by linking occupation data from O*NET to the American Community Survey. I find that lower-wage workers are up to three times less likely to be able to work from home than higher-wage workers. Those with lower levels of education, younger adults, ethnic minorities, and immigrants are also concentrated in occupations that are less likely to be performed from home.
Keywords: J1; I3; 330; COVID-19; stay-at-home orders; work from home; O*NET